1995
DOI: 10.1203/00006450-199511000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Neuronal Injury in the Newborn Lamb: A Comparison of N-Methyl-D-Aspartic Acid Receptor Blockade and Nitric Oxide Synthesis Inhibition on Lesion Size and Cerebral Hyperemia

Abstract: Vol. 38, No. 5, 1995 Printed in U.S.A.The purpose of this study was to compa re the effects of dizocilipine maleate (MK-801) and W -nitro-L-arginine methyl ester (L-NAME) on focal excitotoxic brain injury and associated hemod ynamic response in the newborn lamb. A 27 gauge needle was placed into the right striatum in 28 anesthetized newborn lambs. Seven animals were placed in each group. A negative control group received 0.2 mL of buffered saline, a positive control group received 5 /Lmol of N-methyl-D-aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Indeed, LSCI results show the increase in rCBF in venous component of cerebral circulation in the prestroke stage and, in especially, in the post-stroke time. These results are consistent with clinical data suggesting that hyperperfusion is one of the stroke-associated damages of the brain [44][45][46]. Both LSCI and DOCT imaging show the time-depended progressive changes in the sagittal sinus from the initial stage of stroke until the incidence of brain bleeding.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, LSCI results show the increase in rCBF in venous component of cerebral circulation in the prestroke stage and, in especially, in the post-stroke time. These results are consistent with clinical data suggesting that hyperperfusion is one of the stroke-associated damages of the brain [44][45][46]. Both LSCI and DOCT imaging show the time-depended progressive changes in the sagittal sinus from the initial stage of stroke until the incidence of brain bleeding.…”
Section: Discussionsupporting
confidence: 90%
“…As well, Albayrak et al [29] showed that the cross-sectional area of bilateral ICA and VA and the peak systolic velocity of left ICA increased in patients with hypoxemic, chronic obstructive lung disease. Moreover, it has been reported that hypoxemia caused cerebral vasodilatation via nitric oxide in an experimental study [30]. Clinical reflection of hypoxemia has been shown as decreased RI in asphyxiated babies [31].…”
Section: Discussionmentioning
confidence: 98%
“…Although physiological rapid involution in pulmonary pressure and vascular changes in deed occur after birth, it does not seem very probable that the variation in the postnatal age of the lambs in the different groups [4][5][6][7][8][9][10] might have influenced the findings with re spect to pulmonary pressure. No difference existed between the postnatal age between the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that re duction of nitric oxide production by inhibi tion of nitric oxide synthesis by NLA may reduce postasphyxial reperfusion injury of the brain [9][10][11]. On the other hand, however, nit ric oxide plays a major role in the regulation of pulmonary vascular tone as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation